Impact of Converter Topologies on the Performance of Permanent Magnet Brushless DC Motor - Sivaranjani, S.; C.Ramya, K.; Sheebarani, S.; Karthika, J.; Gomathy, V.; Subha Lakshmi, N. (International Journal of Engineering and Technology, 2018)
Comparative merits over AC motors leads to replacing of other electrical motors by DC motors in applications stretching from high-speed automation to electric motorbikes. However, brushed DC motors are popular for applications where speed needs to be varied or torque needs to be controlled precisely. Because of higher performance and/or reliability, Brushless DC motors are preferred rather than brushed one. Moreover typical brushed DC motor is exposed to sparking during commutation. Electronic commutation via power converters in BLDC motors replaces the mechanical commutation of typical DC motor. It is essential to understand the impact of these converters on the performance of BLDC motors. Hence this paper presents a comparative analysis of various power converters fed Brush Less DC motor.Â The simulation results show that the impact of power converters on the enactment of BLDC motor.Â Â